Product attractiveness and promotional messages: An analysis of their influence on consumer purchase volume - Aprizal Putra; Syafri Naldi; Ogi Rifansyah (PT Aksara Indo Rajawali, 2025)
Companies in the automotive industry need to continually refine their marketing strategies to attract more customers and increase sales as competition intensifies. The goal of this study is to examine how advertising and product quality affect the number of Toyota Raize buyers at Agung Toyota Soetomo Pekanbaru. A quantitative method was applied utilizing an explanatory research design. We got the data by giving surveys to 98 people who had bought a Toyota Raize. We then used Structural Equation Modeling with the Partial Least Square approach to look at the data. The data reveal that promotion has a strong, favorable effect on both how people perceive the product's quality and how many they buy. Likewise, product quality strongly influences sales volume, particularly through performance, durability, and design characteristics. These results show that marketing not only helps people decide to buy something, but also changes how they think about the product's quality, leading to more sales. The corporation should step up its advertising that highlights the benefits of its products and ensure customers know more about them.